Microbial status of burned tropical peat soils: A case study of Perigi peat soil, Ogan Komering Ilir, South Sumatra, Indonesia - Napoleon, Adipati; Salsabila, Nadhira Ghea; Imanudin, M.S.; Soleha, Soleha; Hermawan, Agus; Bakri, Bakri (Journal of Degraded and Mining Lands Management, 2025)
Post-fire tropical peatlands in Southeast Asia face severe ecological degradation, yet the biological dimension, particularly soil microbial abundance as an indicator of ecosystem health, remains understudied. This study aimed to quantify culturable bacterial and fungal populations across different peat layers in a fire-affected peatland in Perigi Village, South Sumatra, Indonesia. Soil samples were collected from two depths  (0-30 cm and 30-60 cm) using a stratified random sampling approach and analyzed with the Total Plate Count (TPC) method on nutrient agar and potato dextrose agar media. Results showed a clear vertical stratification, with microbial populations significantly higher in the surface layer (0-30 cm) than in the subsurface layer (30-60 cm), reaching maximum counts of 2.6×10? CFU g?¹ for bacteria and 8.8×10³ CFU g?¹ for fungi. Sapric peat consistently supported greater microbial abundance than hemic peat, likely due to higher nutrient availability and periodic inputs from recovering vegetation. Regression analysis confirmed a significant negative relationship between peat depth and microbial counts, whereas water table depth had no measurable effect, highlighting the stronger influence of decomposition stage and soil structure over short-term hydrological fluctuations. These findings emphasize the ecological importance of microbial communities in degraded tropical peatlands and suggest that microbial viability metrics offer a cost-effective, biologically relevant indicator for peatland health assessment. Integrating microbial parameters into restoration planning may enhance evidence-based strategies for managing post-fire tropical peat ecosystems.